Elevated Cranial Sutural Complexity in Burrowing Dicynodonts - Kammerer, Christian F. (Frontiers in Ecology and Evolution, 2021)
Relationships between the complexity of the cranial sutures and the inferred ecology of dicynodont synapsids are explored. Simple complexity indices based on degree of sutural interdigitation were calculated for 70 anomodont species and indicate that the naso-frontal sutures of Cistecephalidae, a clade inferred to be dedicated fossors based on aspects of postcranial morphology, are substantially more complex than those of other dicynodonts. The elevated complexity of the naso-frontal suture in this clade is interpreted as being related to compressive forces sustained during burrowing, paralleling the condition in some other fossorial vertebrate groups (e.g., amphisbaenians). The most highly interdigitated sutures in the cistecephalid skull are those oriented transversely to its long axis, which would experience the greatest longitudinal stresses from contact with the substrate. Although it is uncertain to what degree cistecephalid burrowing was based on scratch vs. head-lift digging, it is argued that the head played an important role during locomotion in this group. Increased sutural complexity, rather than cranial fusion, as an adaptation to resisting compressive forces during burrowing may be related to indeterminate growth in dicynodonts.